Factor that influence customer's decision to purchase houses at Bandar Uda Utama, Johor Bahru, Johor / Murnizah Zainal - Zainal, Murnizah (Faculty of Business and Management, 2006)
This research was conducted for the purposed of finding the "Factor that Influence Customer's Decision to Purchase Houses at Bandar UDA Utama, Johor Bahru, Johor". The main objective of this research was to determine the factors that influence customer's decision making toward purchasing houses at Bandar UDA Utama. There are many factors which able to influence any customer's decisions before they decided to purchase their houses. Those factors are the location factor, the price factor, the workmanship factor, community preferences factor, developer factor or infrastructure factor. The respondent of this study would be the residents' at Bandar Uda Utama, Johor Bahru residential only. 150 questionnaires had been distributed to those residents but only 103 questionnaires from the respondents have been picked up due to the some of consequences such as the place is new and it creates difficulties to reach them. The researcher had used probability sampling and simple random sampling as the sampling technique.